The Effectiveness of Probiotics as Adjuvant Therapy in Children with Autism Spectrum Disorder: A Literature Review - FAKHIRAH NAILAH; Alya Raguan Al'Habsyi; Siti Wahyu Windarti (Journal of Diverse Medical Research : Medicosphere, 2026)
Autism Spectrum Disorder (ASD) is a complex developmental disorder associated with gastrointestinal and neuropsychological disturbances. The growing understanding of the gut microbiota role via the gut–brain axis has opened opportunities for using probiotics as adjuvant therapy in managing ASD. This literature review aims to evaluate the effectiveness of  Lactobacillus probiotics as adjunct therapy in children with ASD. A systematic literature search was conducted using the PICO framework and relevant keywords for sources published between 2021 and 2025. Of 22 screened articles, eight studies met the inclusion criteria and were analyzed. Results suggest that  Lactobacillus probiotics show promising effects as adjunct therapy in ASD management. They help restore gut microbiota balance, increase beneficial species such as Bifidobacterium longum and  Lactobacillus spp., and reduce gastrointestinal symptoms including diarrhea and constipation. Neuropsychological improvements include enhanced social responsiveness and reduced anxiety, mediated by microbiota modulation, neuroactive metabolites, and immune system regulation. Additionally, probiotics support neurocognitive and behavioral enhancements via the gut–brain axis, measurable through EEG biomarkers. Minimal side effects and a high safety profile make probiotics a safe and feasible adjunct to conventional treatment. In conclusion, probiotics have potential as a sustainable supportive therapy; however, further high-quality studies with longer durations are required to confirm clinical benefits and fully understand the underlying mechanisms.